Green nanomaterials fostering agrifood sustainability - Bartolucci, Cecilia; Antonacci, Amina; Arduini, Fabiana; Moscone, Danila; Fraceto, Leonardo Fernandes; Campos, Estefania; Attaallah, Raouia; Amine, Aziz; Zanardi, Chiara; Cubillana-Aguilera, Laura M.; Santander, Jose Maria Palacios; Scognamiglio, Viviana (Elsevier, 2020)
The application of nanotechnologies to the agrifood sector provides one of the innovative tools able to support change in a system that, through its intensification and industrialization, currently fails both humans and the environment. The development of green nanotechnology, which exploits biological routes for the synthesis of nanomaterials, and specifically aims to minimize the production of hazardous substances and the input of energy, further underlines the disruptive potential of this technology. Due to the lack of toxic chemicals during their synthesis and to their high adaptability, green nanomaterials thus produced have a wide application domain, and this is reflected in the number of sustainable development goals affected by their use. This review describes the last trends on the eco-designed nanomaterials produced by means of green strategies for application in agriculture, such as nanofertilisers, nanopesticides, and nano(bio)sensors.
Keywords: Green chemistry; nano(bio)sensors; Nanofertilisers; Nanopesticides; Sustainable farming